A Novel Splice-Site Mutation in the GJB2 Gene Causing Mild Postlingual Hearing Impairment - Gandía, Marta; del Castillo, Francisco J.; Rodríguez Álvarez, Francisco J.; Garrido, Gema; Villamar, Manuela; Calderón, Manuela; Moreno Pelayo, Miguel Angel; Moreno, Felipe; del Castillo, Ignacio (My University, 2013)
The DFNB1 subtype of autosomal recessive, nonsyndromic hearing impairment, caused by mutations affecting the GJB2 (connection-26) gene, is highly prevalent in most populations worldwide. DFNB1 hearing impairment is mostly severe or profound and usually appears before the acquisition of speech (prelingual onset), though a small number of hypomorphic missense mutations result in mild or moderate deafness of postlingual onset. We identified a novel GJB2 splice-site mutation, c. -22-2A>C, in three siblings with mild postlingual hearing impairment that were compound heterozygous for c. -22-2A>C and c.35delG. Reverse transcriptase-PCR experiments performed on total RNA extracted from saliva samples from one of these siblings confirmed that c. -22-2A>C abolished the acceptor splice site of the single GJB2 intron, resulting in the absence of normally processed transcripts from this allele. However, we did isolate transcripts from the c. -22-2A>C allele that keep an intact GJB2 coding region and that were generated by use of an alternative acceptor splice site previously unknown. The residual expression of wild-type connection-26 encoded by these transcripts probably underlies the mild severity and late onset of the hearing impairment of these subjects.